Implementation of Information and Communication Technology In Learning Management and Madrasah Administration: Case Study at MTs Khozinatul Ulum Blora - Albin Jaya, Arim Irsyadulloh (QUALITY, 2024)
This research aims to investigate the implementation of Information and Communication Technology (ICT) in learning management and madrasah administration at MTs Khozinatul Ulum Blora. Islamic education faces challenges in adopting technological innovations to improve the efficiency and effectiveness of the management process. A case study was conducted to gain an in-depth insight into the application of ICT in various aspects of educational management at the institution. The research methods used included participant observation, interviews, and document analysis. The results of the study indicate that MTs Khozinatul Ulum Blora has implemented various ICT solutions in learning management and madrasah administration, including the use of academic information systems, online learning, and electronic communication among education stakeholders. Despite facing several obstacles such as limited resources and lack of staff training, the implementation of ICT has made a positive contribution to improving administrative efficiency and the quality of education. This study contributes to the literature on educational management and information technology by presenting concrete findings on the implementation of ICT in the context of Islamic education in Indonesia. The practical implications of the findings of this study can be a reference for other Islamic educational institutions to improve their management through more effective integration of information and communication technology.